Juridical Review of Minimum Service Standards at Manggarai Station - Dhina Setyo Oktaria; Xie Guilin; Deng Jiao; Yuanyuan Wang (Rechtsnormen: Journal of Law, 2023)
Background. Manggarai Station is a large type A train station which is the busiest station. Manggarai Station is under construction and is divided into several stages. As a result of the change in the transit route, it causes passenger discomfort, which is poured on social media. Purpose. This study aims to evaluate the station's performance on changes in the transit route for train travel via the Manggarai station for passengers by the provisions of the applicable regulations. Method. The method used in this research is an empirical legal research study, which is a type of research study that seeks data directly from the field or looks at law in a real sense and studies how the law works in society.33 of 2011 Types, Classes, and Activities at Railway Stations and PM No 63 of 2019 concerning Minimum Service Standards for the Transport of People by Train. Results. The results obtained based on previous research with Importance Performance Analysis still show passenger dissatisfaction, and according to laws and regulations, the public as users of transportation services have the right to submit input related to rail transportation so that PT KCI can provide minimum service standards at stations consisting of security and safety, accurate information, ticket sales services, good condition of station facilities, accessibility, assistance and complaint services. Conclusion. In Ministerial Regulation No. 63 of 2019 concerning Minimum Service Standards for the Transport of People by Train, PT KCI is responsible for KRL passengers at the Manggarai train station and while traveling on the train. This research only discusses the responsibility of PT KCI in providing minimum service standards at manggarai station.